Effects of Whole-Body Vibration-Assisted Training on Lower Limb Blood Flow in Children With Myelomeningocele - Szopa, Andrzej; Domagalska-Szopa, Małgorzata; Siwiec, Andrzej; Kwiecień-Czerwieniec, Ilona (Frontiers in Bioengineering and Biotechnology, 2021)
This study investigated the effectiveness of whole-body vibration (WBV) training incorporated into a conventional physiotherapy (PT) program (WBV-assisted training) in improving blood flow in the lower limbs and range of motion (ROM) in the lower limb joints of children with myelomeningocele (MMC). A total of 31 children with MMC (7–15 years old) underwent a 6-week treatment program consisting of 2 weeks of conventional PT followed by 4 weeks of WBV-assisted training. The assessment comprised two parts: evaluation of lower limb joint ROM and Doppler ultrasonography of the superficial femoral, popliteal, and anterior tibial arteries, and was performed three times for each of the participants (at baseline; after 10 sessions of PT but before WBV-assisted training; and after 20 sessions of WBV-assisted training). Our results showed that WBV-assisted training significantly improved lower limb circulation in patients with MMC, increasing velocity and reducing resistivity in all tested arteries. Moreover, WBV-assisted training alleviated lower-extremity contractures, especially of the knee. Thus, WBV-assisted training is effective as an adjunctive rehabilitation program for improving functional mobility in children with MMC.